Analisis Penerapan Hukum Terhadap Putusan Hakim dalam Perkara Tindak Pidana LGBT di Lingkungan Tentara Nasional Indonesia - M.Jalil Sembiring; Mahmud Mulyadi; Isnaini Isnaini (Mahesa Research Center, 2021)
This study aims to analyze the judge's decision on case number 115-K/PM.1-02/AD/X/2019 at the Military Court I-02 Medan about the different opinions of the panel of judges in the Gay Bisexual and Transgender (LGBT) case in the Indonesian National Army (TNI). TNI). The purpose of this study is to examine the legal regulations regarding criminal punishment for LGBT perpetrators within the TNI and examine the application of penalties for perpetrators who violate the LGBT prohibition within the TNI, as well as to analyze how the basis for applying the law to soldiers who commit LGBT violations within the TNI is. The research conducted is normative legal research that uses a normative juridical approach that takes secondary data by making primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the study, it can be seen that LGBT is a very deviant behavior in which Indonesia has no laws and regulations governing LGBT acts in general and specifically so that the application of punishment is based on Article 281 of the Criminal Code, Article 103 of the Criminal Code, Government Regulation Number 39 of 2010 Article 53 Paragraph (1) letter b Concerning Administration of Indonesian National Armed Forces Soldiers, Kasad Decree Number Kep/330/IV/2018 dated 17 April 2018 concerning Disrespectful Dismissal within the TNI, which was imposed to ensnare LGBT perpetrators within the TNI.